1983
DOI: 10.1007/bf00048970
|View full text |Cite
|
Sign up to set email alerts
|

Invasion in vitro

Abstract: To understand the mechanisms of tumour invasion a number of in vitro assays have been developed, in which test cells (invasive or non-invasive) have been confronted with normal cells or tissues (the host) and cultured in various ways. We will discuss here the methods by which invasion can be judged in such assays. Histology is the method that is used successfully by pathologists for the evaluation of tumour invasiveness in vivo. The major difficulty is that the relationship between the non-invasive counterpart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Mouse class I MHC antigens were isolated by immunoprecipitation with specific anti-H-2 antibody (Figure 8) Morphologically transformed T15 cells cultured and analysed in the continuous presence of DEX, were aggressively invasive in an organotypic invasion assay. In this assay (Mareel, 1983), cell aggregates are confronted with a fragment of normal chick heart tissue. Invasive cells penetrate and destroy the chick heart, but nonmalignant cells do not.…”
Section: Kinetics Of Modification Of Protein Glycosylationmentioning
confidence: 99%
“…Mouse class I MHC antigens were isolated by immunoprecipitation with specific anti-H-2 antibody (Figure 8) Morphologically transformed T15 cells cultured and analysed in the continuous presence of DEX, were aggressively invasive in an organotypic invasion assay. In this assay (Mareel, 1983), cell aggregates are confronted with a fragment of normal chick heart tissue. Invasive cells penetrate and destroy the chick heart, but nonmalignant cells do not.…”
Section: Kinetics Of Modification Of Protein Glycosylationmentioning
confidence: 99%
“…A comprehensive survey of in vitro models of invasion was given by Mareel (61). In general, the reliability of the information yielded by in vitro models improves with their increasing complexity or 'naturalness', which corresponds largely to the progress from two-dimensional to three-dimensional arrangements (62,63).…”
Section: Basic Aspects Of Cell Motility and Tumor Invasionmentioning
confidence: 99%
“…Invasion is required for tumor cells to leave the primary tumor (local invasion), enter the vasculature (intravasation) and for circulating tumor cells to leave the vasculature (extra- vasation). We [34-36, [41][42][43][44] and others [45][46][47][48][49][50] have shown that invasion in vitro and metastasis formation in vivo correlate in a variety of human and rodent cell lines. Thus, development of drugs which inhibit invasion should prevent metastasis.…”
Section: Discussionmentioning
confidence: 99%